Sport-specific measuring and information systems for training control - Wagner, K. (International Journal of Computer Science in Sport, 2006)
For years measuring and informations systems (MIS) have been an indispensable basis for the determination of physical abilities of elite athletes (diagnostic). However, they have been increasingly applied in training (feedback training) in particular for learning and correcting movements (technique training), as well as for the optimization of competition results e. g. in endurance sports (race optimization). In spite of the intense evolution in the field of both software simulation systems and measurement technology for the analysis of competition performance, measuring units will keep their high importance as a component of training control in future. The application of a MIS in high-performance sports is connected with high demands on these systems. Special requirements are e. g. - The resistance of the measuring units against extreme force actions and movement frequencies to be encountered on high performance level - The guarantee of the reliability of the measurement results (comparability of the results, if several identical measuring units are applied; robustness against environmental impacts as temperature or humidity etc.) - Sufficiently precise simulation of the real conditions, so that the results gained can be interpreted in terms of physical abilities (validity). That concerns both the guarantee of the sport-specific movement and the robustness against the actions of the athlete at the measuring unit. - The devlopment of information systems, which can be used smoothly in training, diagnostic or competition. It has to be taken into account that in most cases the individual requirements mentioned above depend on each other. The presentation will focus on systems simulating competition like conditions, since it is not possible to deal with all the different requirements mentioned above in this paper. This goal contains a high standard of objectivity, reliability and validity of the results gained. The following proprietary developments of recent years have been selected as examples.